Current trend in small scale solar updraft tower designs: a review - Marzuki, Omar Faruqi; Teo, Ellie Yi Lih; Mohd Rafie, Azmin Shakrine (East China University of Science and Technology, 2022)
Solar updraft tower is a renewable energy technology which harvest heat generated from the sun. This technology has great potential in locations where sun is available around the year. The main components for this technology are chimney, collector and turbine. The chimney will guide the wind from collector flow upward where the wind will flow through turbine. As carbon footprint becoming more concerning, a small-scale solar tower updraft is one of great solution to alleviate this conundrum. Hence the chimney and collector design play important roles in solar updraft tower performance. Additionally, types of collector ground used and turbine blade technology for harvesting energy can further improve the performance of small-scale solar updraft tower. This paper review current small-scale design solar updraft tower.